Relationship Between Serum Complement C3 Levels and Outcomes Among Patients With Anti-GBM Disease - Zhu, Mengyue; Wang, Jingjing; Le, Weibo; Xu, Feng; Jin, Ying; Jiao, Chenfeng; Zhang, Haitao (Frontiers in Immunology, 2022)
ABSTRACT Background: IgG and complement C3 are generally found to be deposited along the glomerular basement membrane (GBM) in human anti-GBM disease. The pathogenic role of complement activation in kidney damage of anti-GBM disease has been explored in recent years. Therefore, we investigated the relationship between serum C3 and outcomes among patients with anti-GBM disease in this study. Methods: 94 anti-GBM disease patients between January 2004 and December 2020 at National Clinical Research Center of Kidney Diseases Jinling Hospital were retrospectively analyzed, and were divided into the low C3 group and the normal C3 group according to serum C3 levels at diagnosis. 56 of them had undergone renal biopsy. We analyzed the clinical manifestations, laboratory tests, kidney pathology, treatment, and outcomes between the two groups. The primary endpoint was kidney failure. Cox regression and smooth curve fitting of generalized additive mixed model analysis were used to explore the correlation between serum C3 and kidney failure. Outcomes of the two groups were compared by the Kaplan-Meier curve. Results: A total of 94 patients (aged 43.6 ± 16.2, male patients 46%) with anti-GBM disease were enrolled. 26 patients with low C3 levels and 68 patients with normal C3 levels. Compared with the normal C3 group, patients in the low C3 group have a higher proportion of glomerular sclerosis and progressing to kidney failure. Multivariate Cox regression analysis suggested that C3 is associated with kidney outcomes in patients with anti-GBM disease (HR = 0.782, 95%CI = 0.673-0.907, P = 0.001). Smooth curve fitting of generalized additive mixed model analysis indicated that the level of C3 had a linear relationship with the changing trend of kidney failure. The Kaplan-Meier curve showed that there was a statistical difference between the two groups in terms of kidney failure (P = 0.033). Conclusion: The kidney outcomes of anti-GBM disease in the low C3 group were poorer than those in the normal C3 group. The influence of complement C3 on the kidney outcomes of patients with anti-GBM disease may be of clinical relevance.